The Enforcement of Arbitral Awards in Cameroon - Tumnde, Taylor (Social Science Research Network, 2013)
The increase in international trade creates a growing number of disputes between parties from different countries. Arbitration has become the most preferred mechanism to solve disputes in international trade. If a party does not voluntarily comply with an award, the successful party must apply for recognition and enforcement of the award in order to obtain the remedies. Cameroon is one of the major business markets in West and Central Africa, several companies committed to arbitral procedures are likely to have assets in Cameroon. This means that if a party fails to honour an award, an enforcement procedure may begin within a Cameroonian court. The enforcement procedures in Cameroon are sufficient and do comply with international standards. The most used and important instruments for recognition and enforcement are the United Nations Convention on the Recognition and Enforcement of Foreign Arbitral Awards of 1958 and the Uniform Act on Arbitration 1999 in the OHADA territory, to which Cameroon is a signatory State. According to this Convention and the Uniform Act, an arbitral award may be refused enforcement under certain grounds laid down in them. There are various types of arbitral awards contemplated by the Cameroonoan legislature and will be herein examined to see how they can be enforced in Cameroon. An analysis of the legal situation in Cameroon confirms that there are problems associated with the enforcement of arbitral awards. These problems are not, however, connected with the concept of arbitral awards, but rather with the entire judicial system in Cameroon. Even though an enforcing party can do little to overcome these problems, certain measures can be taken in order to ease the enforcement procedure
Keywords: Arbitrage; Arbitragem; Arbitral Awards; Arbitration; Cameroon; Enforcement; OHADA

Normes OHADA et constitutions des Etats membres : conflit en léthargie ou simple temps mort ? - Kagisye, Emmanuel (HAL Open science, 2013)
L’articulation du droit uniforme et des droits nationaux constitue l’une des questions les plus importantes pour le développement d’un système juridique cohérent, particulièrement dans sa composante normative. A cet égard, la supranationalité des normes ohada consacrée par l’article 10 du Traité OHADA et l’interprétation dont en a fait la Cour commune de justice et d’arbitrage constituent une solution de principe . Malheureusement, force est de constater que la supranationalité de normes ohada ne permet pas de les résoudre tous les conflits entre les normes ohada et les normes internes des Etats membres. C’est le cas de normes constitutionnelles des Etats membres qui peuvent entrer en conflit avec les normes primaires et les actes uniformes de l’OHADA.
Keywords: Conflits; Constitutions; Droit OHADA